Practical Applications of Laser Ablation - Yang, Dongfang (IntechOpen, 2021)
Laser ablation refers to the phenomenon in which an intense laser beam irradiates the surface of a solid to induce instant local removal of atoms by a thermal or non-thermal mechanism. Through eight chapters of original research studies and literature reviews written by experts from the international scientific community, this book presents theoretical and experimental aspects of the laser ablation phenomenon for processing material including pulsed laser deposition of thin films, laser surface modification, laser machining and laser nanoparticle formation. It also includes a study of the dynamics of plasmas generated by laser ablation of multi-component materials and an overview of laser-induced breakdown spectroscopy (LIBS) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) techniques for chemical analysis.